A source of gamma rays coincident with the shell of the supernova remnant CTB 80 - Araya Arguedas, Miguel (2021)
CTB 80 (G69.0+2.7) is a relatively old (50–80 kyr) supernova remnant (SNR) with a complex radio morphology showing three extended radio arms and a radio and X-ray nebula near the location of the pulsar PSR B1951+32. We report on a study of the GeV emission in the region of CTB 80 with Fermi-Large Area Telescope data. An extended source with a size of 1.3°, matching the size of the infrared shell associated to the SNR, was discovered. The GeV emission, detected up to an energy of ∼20 GeV, is more significant at the location of the northern radio arm where previous observations imply that the SNR shock is interacting with ambient material. Both hadronic and leptonic scenarios can reproduce the multiwavelength data reasonably well. The hadronic cosmic ray energy density required is considerably larger than the local Galactic value and the gamma-ray leptonic emission is mainly due to bremsstrahlung interactions. We conclude that GeV particles are still trapped or accelerated by the SNR producing the observed high-energy emission when interacting with ambient material.